Evaluation of planting technologies and management in wheat - Carvalho Basilio de Azevedo, Ana Julia (Kansas State University, 2017)
Genotype by seeding rate interaction can play a critical role in wheat (Triticum aestivum L.) yield potential. The objectives of this study were to i) quantify wheat yield response and ii) early-season plant establishment related to the planting technology under diverse seeding rates and with contrasting varieties relative to their tillering ability. Four studies were established at two locations during two growing seasons (2015-16 and 2016-17) at Ashland Bottoms (dryland and conventional till in the first year and no-till in the second year) and at Topeka (irrigated and no-tillage for both years) field research stations (KS, US). Two winter wheat varieties were planted with two different planting systems (singulated and conventional drill) at four different seeding rates (45, 90, 135, and 180 kg ha⁻¹). Early-season measurements consisted of stand counts, canopy coverage (estimated via imagery collection via small-unmanned aerial vehicle systems - sUAVS), determination of early-season gaps within the stand of plants, and spacing between plants. Early season measurements (emergence progression, stand count, and canopy coverage) and biomass did not present differences among treatments. At Ashland, across 2-yrs, single factors seeding rate and genotype significantly impacted yields. Seeding rate factor positively affected yields, ranging from 4.7 to 5.4 Mg ha⁻¹ with seeding rates going from 45 to 135 kg ha⁻¹, respectively. For the genotype factor, the variety WB Cedar (high-tillering) presented an overall yield of 605 kg ha⁻¹ greater than WB 4458 (low-tillering). Across locations, the seeding system did not influence yields for both years of the study. At Topeka, the seeding system significantly influenced yields in 2017, with singulation outyielding the drill system, in 161 kg ha⁻¹. Further research is needed at a farmer-scale testing more winter wheat varieties and focusing on lower seeding rates to better understand the potential benefits of the implementation of this new technology.
Keywords: Seeding rate; Planting technologyWheat